PRAKTEK PEMBUATAN JALAN HUTAN DAN PERMASALAHANNYA DI DAERAH PROPINSI JAMBI - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
An obseroation on road construction practice and its problems in two logging company areas in Jambi Province was conducted in 1990. The spcific playeical condition of the area observed is quite light and, therefore, the coat of road construction is low at Rp 5.84 million/km main road grading.Road densities are 5. 3 m/ha in the first and 11.2 m/ha in the second company area. For these roads. land area used amounts to 111.2'4 ha from the total of 19,940 ha logged-over. area or 0.56% in the first and 401.70 ha from the area of 35,021 ha logged-over area or 1.15% in the second company. The ratio of road length to log volume extracted are 0.21 m/cu.m in the first and 6.69 m/cu.m in the second company.The rate of natural vegetation growth along forest roads is quite high which is very helpful in retarding soil erosion potential of the roads.